2010
DOI: 10.1007/s11524-010-9462-4
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Problem Behavior in Nairobi's Informal Settlements: Applying Problem Behavior Theory in Sub-Saharan Africa

Abstract: Adolescent involvement in problem behaviors can compromise health, development, and successful transition to adulthood. The present study explores the appropriateness of a particular theoretical framework, Problem Behavior Theory, to account for variation in problem behavior among adolescents in informal settlements around a large, rapidly urbanizing city in sub-Saharan Africa. Data were collected from samples of never married adolescents of both sexes, aged 12–19, living in two Nairobi slum settlements (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 23 publications
2
54
1
Order By: Relevance
“…20 Individuals who drop out and get married at an early age by eloping compose group of adolescents having risky behaviors, and it has been found that most of these individuals are female adolescents. 21 In our society, it is known that early marriage is conventionally supported, and these kind of early marriages generally take place with social agreement.…”
Section: Discussionmentioning
confidence: 99%
“…20 Individuals who drop out and get married at an early age by eloping compose group of adolescents having risky behaviors, and it has been found that most of these individuals are female adolescents. 21 In our society, it is known that early marriage is conventionally supported, and these kind of early marriages generally take place with social agreement.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous literature that considers early sex and multiple sexual partnerships as problem behaviors [32], well as literature showing a strong association between sexual behavior and delinquency [30], we also included two items assessing whether the participant had engaged in sexual intercourse by age 15 and whether the participant had ever had multiple sexual partners. Internal consistency of scores on the delinquency scale was assessed using Cronbach’s alpha [33].…”
Section: Methodsmentioning
confidence: 99%
“…There is a need for researchers to consider whether the psychosocial and emotional aspects of menstrual poverty lead to developmental problems, and how this can be mitigated by interventions. Such research is necessary because risk and protective factors in these contexts are likely to be different from the industrialized countries such as the United States where associations between menstrual well-being and developmental impacts have been studied (Ndugwa et al, 2010).…”
Section: Future Researchmentioning
confidence: 99%